Transformation of ram sperm nuclei in oocytes cytoplasm during in vitro fertilization - Dzulfiqor, Y.; Setiadi, M. A.; Karja, N. W. K. (Diponegoro University, 2019)
The aim of present study was to understand the transformation of ram sperm nuclei within oocyte cytoplasm during in vitro fertilization. The oocytes were collected from slaughterhouse ovaries. Before fertilization, the oocytes were maturated in vitro for 24 hours in the incubator with 5% CO2 at 38.5°C. Then the oocytes (n= 635) was fertilized by incubating the oocytes with sperm (5x106 spermatozoa/ ml) for 3, 6, 9, 12, and 15 hours. At the end of incubating period, the oocytes were fixed and stained with aceto-orcein 2% before evaluated under phase contrast microscope. Sperm nuclear transformation was evaluated according to sperm nuclear status of sperm, such as condensation, decondensation, and formation of prepronuclei and pronuclei. Sperm condensation and decondensation were seen at 3 hours after incubation. Prepronuclei and pronuclei were found at 6 hours of incubation. Pronuclei formation was significantly increased in the 9 hours after incubation (P<0.05). The incidence of polyspermia was significantly increased at 12-15 hours after incubation (P<0.05). In conclusion penetration of sperm into oocytes has been occurred at 3 hour of fertilization period. The formation of pronuclei was found at 6 hours after incubation and the incidence of polyspermia was increased when the fertilization period prolonged.